1984
DOI: 10.1111/j.1476-5381.1984.tb16474.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of steroid anaesthetic (alphaxalone) block of acetylcholine‐induced ionic currents

Abstract: 1 The effects of the steroid anaesthetic alphaxalone on acetylcholine (ACh)-induced ionic channels were studied in voltage clamped 'myoballs' in culture. 2 Alphaxalone produced a reversible blockade of the ACh-evoked inward current, ED50 = 6.0 MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…It has been observed that the acetylcholineinduced ionic channels of voltage-clamped myoballs in culture are blocked by high micromolar concentrations of alphaxalone in the open state (Gillo & Lass, 1984). This finding substains the hypothesis of direct interactions between steroid molecules and membrane proteins, i.e., acetylcholine receptors.…”
Section: Introductionsupporting
confidence: 48%
“…It has been observed that the acetylcholineinduced ionic channels of voltage-clamped myoballs in culture are blocked by high micromolar concentrations of alphaxalone in the open state (Gillo & Lass, 1984). This finding substains the hypothesis of direct interactions between steroid molecules and membrane proteins, i.e., acetylcholine receptors.…”
Section: Introductionsupporting
confidence: 48%
“…A somewhat lower IC50 for alphaxalone of 6;tM has been reported for the antagonism of ACh-evoked currents in cultured rat myoballs (Gillo & Lass, 1984).…”
Section: Suppression Ofacetylcholine-evoked Currents By Alphaxalonementioning
confidence: 75%
“…Another pharmacological action of alphaxalone which occurs at higher concentrations (3-100 ,tM) is the depression of excitatory responses to acetylcholine acting on nicotinic receptors (Gillo & Lass, 1984;Cottrell et al 1985).…”
Section: Discussionmentioning
confidence: 99%